Images of Children and Teenagers Victims of Divorce - Destryna Nainggolan; Vonny Victory Sofia; Gerdy Suryahadi (Interdisciplinary Journal of Advanced Research and Innovation, 2025)
This research aims to determine the picture of children and adolescents after divorce. Get a picture of their lives emotionally and physically, in social and educational interactions, and in dealing with conflict. This qualitative research attempts to describe the participants who will be studied based on observations and interviews. This research involved 3 (three) people: one child and two teenagers. The three of them differ in age, gender, education, culture, economy and religion. They are a 10-year-old boy in the 4th grade of elementary school, a 14-year-old girl in the 2nd grade of junior high school, and a 17-year-old boy in the 3rd grade of high school. Researchers also conducted interviews with their mothers to obtain information. The interview aimed to find out more about their post-divorce image. The care and affection of parents after divorce impact them in managing emotions, enthusiasm for learning and overcoming conflicts that occur in their lives.